2014
DOI: 10.1056/nejmoa1312625
|View full text |Cite
|
Sign up to set email alerts
|

Activated STING in a Vascular and Pulmonary Syndrome

Abstract: BACKGROUND The study of autoinflammatory diseases has uncovered mechanisms underlying cytokine dysregulation and inflammation. METHODS We analyzed the DNA of an index patient with early-onset systemic inflammation, cutaneous vasculopathy, and pulmonary inflammation. We sequenced a candidate gene, TMEM173, encoding the stimulator of interferon genes (STING), in this patient and in five unrelated children with similar clinical phenotypes. Four children were evaluated clinically and immunologically. With the ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
1,174
4
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,135 publications
(1,295 citation statements)
references
References 42 publications
36
1,174
4
16
Order By: Relevance
“…autoimmunity in AGS and SLE, targeting the IFN axis by type I IFN blockade may be of potential therapeutic efficacy. Indeed, IFN-α antagonists have been tested in SLE patients in clinical trials with promising results (55), while JAK inhibition was recently reported to ameliorate symptoms in patients with the type I IFNdriven STING-associated vasculopathy (56). TREX1 has been implicated in the restriction of retroelements by metabolizing reverse-transcribed retroelement-derived RNA (46), raising the possibility that retroelement-derived RNA/DNA hybrids may act as substrates of RNase H2.…”
Section: Discussionmentioning
confidence: 99%
“…autoimmunity in AGS and SLE, targeting the IFN axis by type I IFN blockade may be of potential therapeutic efficacy. Indeed, IFN-α antagonists have been tested in SLE patients in clinical trials with promising results (55), while JAK inhibition was recently reported to ameliorate symptoms in patients with the type I IFNdriven STING-associated vasculopathy (56). TREX1 has been implicated in the restriction of retroelements by metabolizing reverse-transcribed retroelement-derived RNA (46), raising the possibility that retroelement-derived RNA/DNA hybrids may act as substrates of RNase H2.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent exciting discovery related to gene mutations and inflammatory vasculopathy is STINGassociated vasclulopathy. 35 The gene mutations in exon 5 of TMEM173, encoding the stimulator of interferon genes (STING) were found in six patients with systemic inflammation, peripheral vascular inflammation and pulmonary manifestations. DVT was not observed in the six patients studied.…”
Section: Mechanisms Linking Inflammation and Venous Thrombosismentioning
confidence: 99%
“…Newly recognized diseases such as early-onset stroke and vasculopathy associated with mutations in adenosine deaminase 2 (ADA2) and activated stimulator of interferon genes (STING)-associated vasculopathy with onset in infancy (SAVI) are both mimics of CNS vasculitis [69][70][71]. ADA2 mutations have also been described in children with a polyarteritis nodosa [70].…”
Section: Cns Vasculitis In New Monogenic Diseasementioning
confidence: 99%
“…Treatment with etanercept has been successful in patients with ADA2 mutations [69]. JAK inhibitors have been shown to be effective in vitro in SAVI [71].…”
Section: Cns Vasculitis In New Monogenic Diseasementioning
confidence: 99%